2021
DOI: 10.3390/antibiotics10020158
|View full text |Cite
|
Sign up to set email alerts
|

The Glomerular Filtration Rate Estimators in the Pharmacokinetic Modelling in Acute Kidney Injury: An Observational Study

Abstract: The glomerular filtration rate (GFR), according to which the drug dose for patients with chronic kidney disease (CKD) is adjusted, is computed with estimators (eGFR) that are developed specifically for CKD. These particular types of estimators are also used in population pharmacokinetic (pop PK) modelling in drug development. Similar approaches without scientific validation have been proposed for patients with acute kidney injury (AKI), yet it is uncertain which specific eGFR should be used for drug dosing or … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1

Citation Types

0
2
0

Year Published

2021
2021
2022
2022

Publication Types

Select...
3

Relationship

0
3

Authors

Journals

citations
Cited by 3 publications
(2 citation statements)
references
References 42 publications
0
2
0
Order By: Relevance
“…This formula used body weight to calculate creatinine clearance in mL/minute (21). Alteration in eGFR is connected to creatinine clearance from collected urine after 24 hours and Gentamycin clearance (22,23). A multicenter prospective study found that the Cockcroft-Gault formula could be used to predict the prognosis of a cardiovascular event, specifically mortality and bleeding (24).…”
Section: Resultsmentioning
confidence: 99%
“…This formula used body weight to calculate creatinine clearance in mL/minute (21). Alteration in eGFR is connected to creatinine clearance from collected urine after 24 hours and Gentamycin clearance (22,23). A multicenter prospective study found that the Cockcroft-Gault formula could be used to predict the prognosis of a cardiovascular event, specifically mortality and bleeding (24).…”
Section: Resultsmentioning
confidence: 99%
“…9,45 In contrast, our study represents a proof-of-concept for employing exposure data from an exclusively renally eliminated drug in both obese and nonobese individuals to evaluate predictors and prediction methods of GFR/creatinine clearance. The predictive performance of GFR/creatinine clearance prediction methods has been evaluated before via the elimination of drugs predominantly eliminated via glomerular filtration, such as vancomycin 46,47 (critically ill patients) or gentamicin 48 (geriatric patients). However, accuracy of elimination of vancomycin as GFR/creatinine clearance reference in obese and nonobese patients was compromised by tubular secretion and reabsorption.…”
Section: Identification Of Glomerular Filtration Categoriesmentioning
confidence: 99%